2003
DOI: 10.1111/j.1532-950x.2004.04007.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Examination of Third Metacarpal/Third Metatarsal Bone Failure Surfaces in Thoroughbred Racehorses with Condylar Fracture

Abstract: Accumulation and coalescence of branching microcracks into arrays or clusters appears to eventually lead to the development of macroscopic subchondral cracks in the condylar groove and initiation of a condylar fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 27 publications
2
51
0
1
Order By: Relevance
“…Lameness in the non-racing horses may have induced a state of disuse and affected bone remodeling. Accumulation of microdamage and development of naturally occurring fatigue fractures is site-specific, 13,14,19 presumably because these bone regions are exposed to particularly high cyclic stresses. We did not perform ESWT on limbs with active dorsal metacarpal disease, which would likely have more microcracks in the dorsal cortex and, therefore, may be more susceptible to induction of additional microdamage by ESWT and associated adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lameness in the non-racing horses may have induced a state of disuse and affected bone remodeling. Accumulation of microdamage and development of naturally occurring fatigue fractures is site-specific, 13,14,19 presumably because these bone regions are exposed to particularly high cyclic stresses. We did not perform ESWT on limbs with active dorsal metacarpal disease, which would likely have more microcracks in the dorsal cortex and, therefore, may be more susceptible to induction of additional microdamage by ESWT and associated adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Microcracks in bone and the associated adaptive remodeling response are key factors in the disease mechanism for catastrophic fatigue fracture in the Thoroughbred racehorse. 13,14 Accordingly, we wanted to determine if ESWT altered microdamage in equine compact bone. We found that ESWT and racing and training activity were both associated with small increases in microcracking in compact bone of MC3/MT3.…”
Section: Discussionmentioning
confidence: 99%
“…The third metacarpal bone (MC3) is a common site of fracture in racehorses [4,5], with lateral condylar fractures often accounting for the majority of these injuries [6][7][8]. Studies suggest that condylar fractures are the end result of a chronic pathological process that affects the articular cartilage and subchondral bone [4,[9][10][11][12][13][14]. Subchondral bone contributes to the majority of stress absorption within a joint [15] and the stress of exercise increases the stiffness [16] and density [17][18][19] of subchondral bone.…”
Section: Introductionmentioning
confidence: 99%
“…Vaughan and Mason (1975) reiterated the suspicion that "some incoordinate movement" caused condylar fracture, but of the 9 condylar fractures in their study, 8 came from horses that were reported to be galloping, cantering or finishing a race in the normal fashion when fracture occurred (Vaughan and Mason 1975). No subsequent study has confirmed Rooney's hypothesis, and condylar fractures are now considered stress fractures resulting from chronic bone damage because they occur after cyclic loading within the normal range (Riggs 1999;Riggs 2002;Stepnik, Radtke, Scollay, Oshel, Albrecht, Santschi, Markel and Muir 2004). Despite the changing opinion amongst researchers and lack of supporting evidence, Rooney continued to publish his hypothesis as late as the mid-1990's (Rooney and Robertson 1996).…”
Section: 8 5 Pathogenesismentioning
confidence: 99%
“…Stepnik, Radtke and Scollay (2004) claim to have observed branching arrays of microcracks at the failure surface of catastrophic Mc3 fractures by scanning electron microscopy (SEM) (Radtke, Danova, Scollay, Santschi, Markel, Da Costa Gomez and Muir 2003;Stepnik, Radtke, Scollay, Oshel, Albrecht, Santschi, Markel and Muir 2004). A thin layer of ACC was reported to overlay remodelled, dense subchondral bone in which branching arrays of microcracks were seen.…”
Section: 8 5 Pathogenesismentioning
confidence: 99%